2018
DOI: 10.1007/978-3-030-00794-2_55
|View full text |Cite
|
Sign up to set email alerts
|

Towards a French Smart-Home Voice Command Corpus: Design and NLU Experiments

Abstract: Despite growing interest in smart-homes, semantically annotated large voice command corpora for Natural Language development (NLU) are scarce, especially for languages other than English. In this paper, we present an approach to generate customizable synthetic corpora of semantically-annotated French commands for a smart-home. This corpus was used to train three NLU models-a triangular CRF, an attention-based RNN and the Rasa framework-evaluated using a small corpus of real users interacting with a smart home.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
0
14
1
2
Order By: Relevance
“…The intent classifier we propose is close to the one of Liu et al [14]. Both classifiers have shown close performances on a voice command task [17], [18]. Although the classifier of Liu et al [14] has shown slightly better performances, it relies on aligned data while our intent classifier is independent from aligned data.…”
Section: Related Workmentioning
confidence: 57%
See 1 more Smart Citation
“…The intent classifier we propose is close to the one of Liu et al [14]. Both classifiers have shown close performances on a voice command task [17], [18]. Although the classifier of Liu et al [14] has shown slightly better performances, it relies on aligned data while our intent classifier is independent from aligned data.…”
Section: Related Workmentioning
confidence: 57%
“…Since the amount of real data is too small for training, the corpus generator of Desot et al [17] was used to produce training data automatically labeled with intents, slot and value labels for the SLU experiments. On top of that several syntactic variants per sentence are provided (table II).…”
Section: B Data Augmentation Via Artificial Data Generationmentioning
confidence: 99%
“…Although our seq2seq NLU model is close to the one of Liu et al [17] showing high performances on a voice command task using aligned data [19], it should learn to associate several words to one slot label without aligned data. For instance, from "Turn on the light" (Allume la lumière) the model generates the sequence intent[set device], action[turn on], device[light], without specifying the slot associated with the definite article.…”
Section: Pipeline Slumentioning
confidence: 93%
“…For that reason we used standard expert-based NLG [28]. The corpus generator of Desot et al [19] produced training data automatically labeled with intents and slots. It was built using the open source NLTK python library to which feature-respecting topdown grammar generation was added.…”
Section: Data Augmentation Using Artificial Data Generationmentioning
confidence: 99%
See 1 more Smart Citation